PENGARUH INOVASI PRODUK DAN MEDIA SOSIAL TERHADAP KEBERHASILAN USAHA DAGANG DI PASAR HELEZALULU KECAMATAN LAHUSA - Primadolius Ndruru (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The purpose of this study was to determine the influence of product innovation and social media on the success of trading businesses at Helezalulu Market, Lahusa District. This study used quantitative research. The population and sample size were 33 respondents. The data used were primary data, and the data sources were business owners. The data analysis method used was multiple regression analysis. Based on the results, it was determined that product innovation and social media simultaneously had a positive and significant influence on the success of trading businesses at Helezalulu Market, Lahusa District. The recommendations of this study are: (1) To increase business success, every trader should use social media applications to assist entrepreneurs in promoting all marketed products. (2) It is recommended that every business actor using social media includes notes such as a cell phone number so that communication is faster and more efficient. (3) Business actors should be more creative in designing various products to increase business success. (4) To create new products, it is very necessary for entrepreneurs to have good ideas to attract buyers' attention.